PENERAPAN KHIYĀR TA‘YIN DALAM PRAKTIK JUAL BELI BAN MOBIL BEKAS DI ARENA BAN BANDA ACEH - Rezka (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2022)
Khiyār ta'yiń is the right to choose for buyers in determining goods of different quality in buying and selling. Apart from that, khiyār also has the authority to withhold or accept trade that occurs before the sale and purchase is complete, whether in agreement or qabul. The focus of this research is on the concept of khiyār ta'yiń in muamalah fiqh and the application of khiyār ta'yiń to the buying and selling of used car tires at the Banda Aceh Tire Arena. The type of research used in this research is sociological juridical, while the nature of this research uses descriptive analysis methods, collecting primary data through interviews and documentation. The research results showed that the concept of khiyār ta'yiń in muamalah fiqh regarding buying and selling used tires is based on what is contained in the Al-Qur'an, Hadith and the opinions of ulama. Buying and selling used tires is permitted provided that the conditions of sale and purchase are met and mutual agreement is met between the seller and the buyer. In this case, the seller gives the buyer a choice of quality of goods. The choice of goods provided includes 3 choices, namely good, medium and low quality goods. Each quality option available also has a different price, as well as applying a time limit for the validity of khiyār ta'yiń. Then the application of khiyār ta'yiń to the buying and selling of used car tires at the Banda Aceh Ban Arena in relation to selling products that match the quality desired and needed by consumers is completely in accordance with the concept of khiyār ta'yiń, namely choosing one of the 3 types of goods will be purchased according to the level of quality it has, then the second condition is that the type of goods to be selected has a price difference from other types and the price must also be known for certain, and the last condition is that the time is limited according to the agreement that was made when the transaction occurred. between sellers and buyers. These three aspects have been completely fulfilled.